1984
DOI: 10.1007/bf02450370
|View full text |Cite
|
Sign up to set email alerts
|

Soil acidity factors and nodulation ofTrifolium repens

Abstract: Rhizosphere Root elongation Root hairs Trifolium repens White clover Summary Effects of factors associated with soil acidity (low pH, low calcium, high aluminium and high manganese) on the Trifolium repens-Rhizobium trifolii symbiosis were investigated under laboratory conditions using an axenic solution:culture technique. 200 uM manganese increased root elongation in the range pH 4.3-5.5, but had no effect on root hair formation, the number of Rhizobium in the thizosphere, or nodule formation. Root elongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 25 publications
1
27
1
1
Order By: Relevance
“…Further, Mn toxicity has been reported not to affect root hair growth (Wood et al, 1984), as was evidenced in the current study by the good root hair growth observed in the low Cu solutions. This Mn toxicity is due to the displacement of Mn from the resin by other cations with greater affinities for the resin's binding sites (such as Cu 2+ , Ca 2+ , and Zn 2+ ) (manufacturer's guidelines).…”
Section: Discussionsupporting
confidence: 47%
“…Further, Mn toxicity has been reported not to affect root hair growth (Wood et al, 1984), as was evidenced in the current study by the good root hair growth observed in the low Cu solutions. This Mn toxicity is due to the displacement of Mn from the resin by other cations with greater affinities for the resin's binding sites (such as Cu 2+ , Ca 2+ , and Zn 2+ ) (manufacturer's guidelines).…”
Section: Discussionsupporting
confidence: 47%
“…For example, curling of inoculated lucerne {Medieago sativa L.) root hairs was found to be dependent on pH at solution Ca concentrations ^ 400 //M (Munns, 1970). Also, root hair formation of white clover {Trifolium repens L.) was inhibited at pH 4-3 when the Ca concentration was < 500 //M, but was independent of Ca concentration at higher pH (Wood, Cooper & Holding, 1984). While the precise role of Ca in protecting root hairs from toxicities of H^ and other ions is not fully understood, Ewens & Leigh (1985) have suggested that Ca is involved in the maintenance of an electrochemical gradient across the root tip.…”
Section: Dj Brady and Othersmentioning
confidence: 99%
“…Genotypes NaCl ( Means followed by the same letter within a column are not significantly different (P≤0.05) using the least significant difference (LSD) test rhizobia strain effect on common bean has been reported in previous works (Wood et al 1984;Peoples et al 1995;Ndakidemi et al 2006;Bambara and Ndakidemi 2010). Inoculation with these local rhizobia strains, especially RhM11, could play a crucial role in plant growth and nodule biomass improvement under salinity constraint when plant growth depends on SNF.…”
Section: Strainsmentioning
confidence: 93%